Analysis of Data Collection and Measurement of Progress in The English Education Curriculum - Fajariah Fajariah; Hesty Widiastuty; Zaitun Qamariah (Lembaga Pengembangan Kinerja Dosen, 2023)
This article analyzes the importance of data collection and measurement of progress in the English education curriculum. Accurate data collection and effective measurement methods play an important role in evaluating the effectiveness of the English education curriculum. Some of the relevant data collection methods include tests and examinations, use of portfolios, and class observations. Meanwhile, progress measurement methods include grades, performance scales, formative tests, project assessments, and self-evaluations. By using these methods, teachers can get comprehensive information about students' progress in English, which can then be used to design appropriate teaching strategies. Accurate data collection and effective measurement of progress will provide significant benefits in improving students' English learning